2019
DOI: 10.1071/rd18227
|View full text |Cite
|
Sign up to set email alerts
|

Comparative serum proteome analysis reveals potential early pregnancy-specific protein biomarkers in pigs

Abstract: In this study, the comparative serum proteome profile of Day 5, 12 and 16 of gestation, representing three early embryonic events, namely formation, elongation and implantation of blastocysts, and non-pregnant control were explored by a label-free quantitation-based mass spectrometric approach to identify early pregnancy biomarkers in pigs. A total of 131 proteins were identified with respect to different groups, out of which 105 were found to be differentially expressed proteins (DEPs). Among the DEPs, 54 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…This protein plays a key role in inflammation, permeability, angiogenesis, tumor metastasis, and cell proliferation (Rauch et al, 2013). Previous studies also hypothesized that VWF could be important in maternal recognition and embryogenesis of pregnancy in cattle (Beindorff et al, 2010), buffaloes (Balhara et al, 2014), and pigs (De et al, 2019). Furthermore, the expression of CALD1 and FBLN-5 was unique in the serum of early pregnant mares.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This protein plays a key role in inflammation, permeability, angiogenesis, tumor metastasis, and cell proliferation (Rauch et al, 2013). Previous studies also hypothesized that VWF could be important in maternal recognition and embryogenesis of pregnancy in cattle (Beindorff et al, 2010), buffaloes (Balhara et al, 2014), and pigs (De et al, 2019). Furthermore, the expression of CALD1 and FBLN-5 was unique in the serum of early pregnant mares.…”
Section: Discussionmentioning
confidence: 98%
“…The functional classification of DEPs shows the similar BPs of metabolic process as previous reports of uterine proteome on horses (Smits et al, 2018), and serum proteome on donkeys (Deng et al, 2020) and pigs (De et al, 2019). Meanwhile, binding and extracellular region was the most represented MF and CC terms, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of pigs indicated that gene expression of glutathione peroxidase 1 ( GPX1 ), microsomal glutathione S-transferase 1 ( MGST1 ) and cytoplasmic copper-zinc superoxide dismutase ( SOD1 ) increased during conceptus elongation ( Blomberg et al., 2005 ). Similarly, a serum proteome-based study of pigs also demonstrated that GPX3 and copper-containing acute-phase protein increased during this period ( De et al., 2019 ). Mun et al.…”
Section: Activation Of Redox Pathways In Porcine Conceptus Trophectodermmentioning
confidence: 92%
“…To enrich LAPs, ProteoMiner TM kit (Bio-Rad, Hercules, CA, USA) with hexapeptide ligand library was employed according to the manufacturer's instruction. Protein sample was subjected to nano ESI-LC MS/MS analysis thrice (technical replicates) for their identification at Valerian Chem Private Limited, New Delhi, India, following the procedure mentioned in our previous study (De et al 2019).…”
mentioning
confidence: 99%
“…Proteins including glutathione peroxidase, pregnancy zone protein, thrombospondin-1, serpins, mannose-binding lectin-C etc. have been reported to be potential biomarkers for physiological processes like pregnancy (Jalali et al 2016, Kolakowska et al 2017, De et al 2019. Whereas, vitronectin was proposed as potential biomarker to predict feed efficiency in young pigs (Grubbs et al 2016).…”
mentioning
confidence: 99%